Kasvatusympäristön vaikutus siniketun (Alopex lagopus) hyvinvointiin - Korhonen, Hannu T; Jauhiainen, Lauri; Niemelä, Paavo; Harri, Mikko; Sauna-aho, Raija (Suomen maataloustieteellinen seura, 2002)
v ok http://www.agronet.fi/maataloustieteellinenseura/julkaisut/esitelmä/kr03korhonen.pdf